Angiofibrolipoma of the larynx: Case report and literature review. Issue 4 (7th October 2015) - Bochnia, Marek; Grabowski, Krzysztof; Zalewska, Agata; Morawska–Kochman, Monika
Abstract: Background: Angiofibrolipomas are one of the rarest variants of lipomas. Laryngeal origin of lipomatous tumors is also very rare. Methods: The nature and severity of symptoms depend on the location and the size of the laryngeal tumors. However, pedunculated of a 28‐cm long tumor with the point of origin on the left arytenoepiglottic fold reached down to the esophagus and. in spite of slight dysphagia. remained asymptomatic for many years. In this case, a narrowing of the digestive tract was masked by an adaptation to the presence of a slowly growing mass. Results: After surgical removal of the tumor and 18‐month follow‐up, the patient remains asymptomatic. Nonetheless, taking into consideration a possibility of recurrence or malignance, a postoperative regular 5‐year follow‐up was recommended. Conclusion: This case report illustrates the successful transoral resection of a polypoid‐shaped angiofibrolipoma of the larynx. An easy and safe endoscopic procedure seemed to be successful in the case described. © 2015 Wiley Periodicals, Inc. Head Neck 38: E81–E83, 2016